Il volume del colore - Garcia-Marques, Francesca (1995)
Museo de arte contemporáneo en <Monterrey>, por Legorreta Arquitectos.
Keywords: LEGORRETA, RICARDO; LEGORRETA, VÍCTOR; CASTRO, NOE; VILLEL, CARLOS; KRAYER, ERICA; PINEDA, JOAQUÍN; MEXICO; MUSEOS; MUSEOS DE ARTE